Preparation of Positively Charged Membrane from Natural Rubber Latex Blending with Chitosan - Taweepreda, Wirach; Tuaybut, Supawadee; Puangmanee, Sineenart; Khoa, Tran Dang (Communications in Physics, 2014)
Film formation of natural rubber latex (NRL) blended with various concentrations of chitosan was investigated. Atomic force microscopy (AFM) images clearly showed that the NRL film covered chitosan phase. Roughness of the films which was calculated from AFM image increases with increasing chitosan concentration. Miscibility of NRL and chitosan in solution was investigated by using dynamic mechanical thermal analysis (DMTA) and found that chitosan incorporated with NRL less than 40 weight percentage (wt%) was partially miscible. Films of the chitosan blending with higher NRL contents exhibited two peaks of glass transition temperatures. Interfacial polarization and dielectric properties of polymer films were improved with increasing NRL contents. Chemical structure of the blends was characterized by using attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR)